The implementation of lesson study as a tool to improve the students' higher order thinking skill on trigonometric material regarding creative thinking skill. (June 2020) - Hadianto, N; Hobri,; Irvan, M
Abstract: The development of lesson study-based learning tool where students are able to involve directly in the learning so it is expected to improve their creative thinking skill. This research aimed at developing lesson study-based learning tool to help the students improve their creative thinking skill at SMK Darussalam in Trigonometry material validly, practically and effectively. This research used Plomp development model research design consisting of 3 phases covering: (i) Preliminary Research, (ii) Prototyping Phase and (iii) Assessment Phase. This research was the learning tool development research and experimental research by using Quasi Experimental Design method and Non-equivalent Post-test Only Control Group Design. In this research, the sampling technique used was simple random sampling. Out of 7 population classes, 2 sample classes were selected namely class X TKJ 1 as the experimental class which was given the treatment by using teaching material development and class X TKJ 2 as the control class by using direct learning. The data analysis technique used descriptive analysis to test the validity, practicality and effectivity as well as through mix method analysis to analyze the results of the students' learning achievement between the experimental and control classes. The results of this research revealed that: in the pre-test phase, from the experimental class, there were 3 students who belonged to L4 level, 1 student from the control class and in the post-test phase, from the experimental class, there were 8 students who were at L4 and only 1 student from the control class. With a significance of [t=1.15 and df = 61, p>0.05] in the pre-test phase and the value of [t=4.04 and df = 61, p<0.05] in the post-test phase and in the regression test, the values of tcount was 4.649 and ttable in degrees of freedom (df) = N − 2 = 33 − 2 = 31 with a significance of 95% as much as 1.196 with a determination of tcount > ttable (8.296 > 1.196) therefore Ho was accepted and Ha was rejected with a provision that there was a significant influence of lesson study method on the students' creative thinking skill.